Efektifitas Pemberian Rebusan Daun Katuk terhadap Produksi ASI pada Post Partum Hari Ketiga - Aprilian, Evy; Veronika Widiatrilupi, Raden Maria (Mando Care Jurnal, 2025)
Early breastfeeding is beneficial for both mother and child because breast milk plays an important role in supporting the growth, well-being, survival of the baby, causing uterine contractions and preventing postpartum hemorrhage. Based on the results of the 2017 Indonesian Demographic Health Survey (SDKI), only 3.7% of babies received breast milk on the first day, while breastfeeding in the first 2 months of age was 64%, which then decreased in the following period of 3 months of age 45.5%, at the age of 4-5 months 13.9% and 6-7 months 7.8%. Meanwhile, there was an increase in the use of breast milk substitutes (PASI) commonly called formula or formula milk threefold in the period 2015 from 10.8% to 32.4% in 2017. The purpose of this study was to determine the Effectiveness of Giving Katuk Leaf Decoction on Breast Milk Production on the Third Day of Postpartum at the Bantur Community Health Center UPT, Malang Regency. This type of research is quasi-experimental with a nonequivalent control group design. The sample in this study amounted to 30 people consisting of 15 experimental groups and 15 control groups. Conducted in May 2025. The results of the study showed that the average breast milk adequacy in breastfeeding mothers in the experimental group before giving katuk leaves was 6.60 and after giving katuk leaves was 8.47. In conclusion, giving katuk leaves has been proven effective in increasing breast milk adequacy in breastfeeding mothers.